The Features of Diffusion and Mechanical Waves Interaction at the Initial Stage of Metal Surface Treatment by Particle Beam under Nonisothermal Conditions - Parfenova E. S. Elena Sergeevna (Electrophysical and Electrochemical Methods and Technologies of Materials Treatment, 2016)
Title screen